The adaptation of social responsibility reporting within a multi-national corporation: a multi-level study - Gutierrez-Huerter O, Gabriela (2016)
The purpose of this research is to study the adaptation of corporate social responsibility reporting (CSRR), an outcome of its vertical transfer between the HQ and subsidiaries of a multi-national corporation (MNC). The transfer of practices and policies by MNCs across their geographically dispersed units has been a central concern in the IB literature which has provided rich insight into the determinants of practice adoption by subsidiaries. Here the seminal contributions by Kostova and colleagues (Kostova, 1999; Kostova & Roth, 2002; Kostova & Zaheer, 1999) have paved the way to an understanding of the potential barriers to the transfer of practices across units within an MNC. Nevertheless, despite subsequent contributions recognising that adaptation is a necessary component in such transfers (e.g., Jensen & Szulanski, 2004), the field has shown “signs of intellectual hegemony” (Ferner, Edwards, & Tempel, 2012: 164) dominated by the Kostovian premises. These propositions, drawing predominantly from new institutionalism, have provided a representation of the effects of host country requirements and parent company expectations on subsidiary responses revolving around the notion of “institutional duality”. Yet, significant gaps remain in our understanding of the interaction of the determinants across different levels of analysis influencing the adaptation of the transferred practice at the subsidiary level. Against this background and recent calls to question the traditional conformity-driven explanations influenced by the Kostovian premises (Bello & Kostova, 2014; Ferner et al., 2012; Kostova, Marano, & Tallman, 2016), this thesis shifts away from the deterministic view of institutions constraining subsidiaries (Saka-Helmhout & Geppert, 2011) and the neglect of individuals’ agency to shape and modify practices that has prevailed in the transfer of practices literature. It does so by adopting an eclectic theoretical approach capitalising on the three schools of institutional theory: the new, the comparative/historical and Scandinavian and leveraging insights from multi-level approaches in the transfer of practices and CSR literature (e.g., Aguilera, Rupp, Williams, & Ganapathi, 2007; Jamali & Neville, 2011; Kostova, 1999; Kostova & Roth, 2002, Lee 2011). Instead of limiting the discussion to the duality of home and host country institutional pressures, this thesis addresses the influence and interaction of three levels of analysis: the institutional (the national business system and organisational field pressures), the organisational (the MNC’s mechanisms governing the transfer of CSRR and the subsidiaries’ absorptive capacity) and the individual (translation strategies adopted by boundary-spanners) on the adaptation of CSRR. To this end, the thesis uses a qualitative case study with multiple embedded units of a UK-based MNC in the information systems’ industry, FINEST1. The case study is informed mainly by 47 semi-structured interviews conducted across the French, Danish, Dutch, American and Brazilian subsidiaries as well as complementary secondary data (annual and CSR reports, website information and internal documents), which provide rich empirical dataset. The thesis is underpinned by a critical realist philosophy which is a viable paradigm for conducting explanatory multi-level research since it is offers the possibility to investigate social phenomena in a holistic manner, rejects the determinism and reductionism that are inherent to the regularity model of scientific explanation (Welch, Piekkari, Plakoyiannaki, & Paavilainen-Mäntymäki, 2011) and is consistent with the theorisation of the environment as a nested milieu, where social objects by virtue of their structure have causal powers. The findings of this research shed light on the heterogeneous adaptation of CSRR and the variety of subsidiaries’ strategic responses associated with it. Four adaptation configurations with different levels of implementation, internalisation, integration and fidelity are identified: intentional decoupling, proactive adaptation, unintentional decoupling and ceremonial adaptation. The multi-level framework proposed in this thesis contributes to the transfer of practices literature by providing a powerful tool to study the complex network of mechanisms that explain those four adaptation configurations and the contingent conditions under which they are expected to occur. The framework shows that the configuration of the adaptation of CSRR is mostly explained by the level of development of the absorptive capacity and the type of translation strategy devised by the boundary-spanner. The study reveals that a well-developed absorptive capacity and the hybridisation translation strategy offsets the barriers of the institutional environment on the adaptation of the transferred practice. Conversely, if the subsidiaries’ absorptive capacity remains underdeveloped and the boundary spanners devise either a replication or replacement translation strategies, a favourable institutional environment is not sufficient to trigger an enhanced adaptation supporting the view that national institutions along with the organisational field pressures can constrain or enable the adaptation of CSRR, but they are not “absolute” (Edwards, Colling, & Ferner, 2007). The findings thus expose the key role of the parent MNC in using an appropriate mix of social, control and integration mechanisms that enhance the absorptive capacity and complement the existing stocks of knowledge of its subsidiaries and simultaneously support the translation role of boundary spanners. The cross-disciplinary approach of this research allows making further contributions to the CSRR, comparative and multilevel CSR literatures. Finally, examining the multi-level determinants, this thesis allows proposing actionable recommendations not only for MNCs’ managers but for actors involved in business & society relations such as government and policy makers.